A Cultural Semiotic Aesthetic Approach for a Virtual Heritage Project: Part B—Evaluation and Design for Virtual Heritage and Theoretical Extensions - Voutounos, Chrysanthos; Lanitis, Andreas (My University, 2018)
Continuing from Part A (2016), in which we discuss the semiotic foundation for designing a virtual museum of Byzantine art, Part B presents an applied methodology for the representation of cultural artifacts through virtual technologies and semiotic techniques. We discuss how our semiotic model, case study semiosphere, contributes to design and evaluation research of such unique art-form representation and why the approach contributes as a whole to the field of Virtual Heritage (VH). Theorizing further the design implications integrating the overall approach including the evaluation experiment of three VH applications with the participation of young users and its semiotic analysis, we formulate design guidelines that can be applied also to other types of cultural heritage and art.
Keywords: Semiotics; Aesthetics; Semiosphere; Virtual Heritage; Byzantine art